2010
DOI: 10.1111/j.1600-0536.2010.01828.x
|View full text |Cite
|
Sign up to set email alerts
|

Preservatives and fragrances in selected consumer-available cosmetics and detergents

Abstract: Several preservatives and fragrances with well-known skin-sensitizing potential were common in the examined product types. Such products may be used several times a day by consumers and workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
128
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(140 citation statements)
references
References 25 publications
(24 reference statements)
7
128
2
3
Order By: Relevance
“…Yazar et al reported that the detection frequency of 2-phenoxyethanol in cosmetics and detergents was detected 39% and 19%, respectively. 18 In comparison to our result, the detection frequency of 2-phenoxyethanol seems to follow the similar trend. 2-Phenoxyethanol (< 1%) was used as a preservative in all the samples.…”
supporting
confidence: 74%
“…Yazar et al reported that the detection frequency of 2-phenoxyethanol in cosmetics and detergents was detected 39% and 19%, respectively. 18 In comparison to our result, the detection frequency of 2-phenoxyethanol seems to follow the similar trend. 2-Phenoxyethanol (< 1%) was used as a preservative in all the samples.…”
supporting
confidence: 74%
“…Izotiazolinony również były i są wykorzystywane w licznych produktach przemysłowych, takich jak farby (emulsje lateksowe), farby drukarskie, tonery, lakiery, chłodziwa i płyny do obróbki metali, paliwa odrzutowe, kleje, pestycydy, w procesie produkcji papieru, kontroli jakości mleka, w radiografii i do dezynfekcji wody w basenach (11)(12)(13). Istnieją pojedyncze dane o rozpowszechnieniu użycia izotiazolinonów na rynku europejskim (12, [14][15][16] …”
Section: I Mi Jako śRodki Konserwująceunclassified
“…Most cosmetic products contain fragrances, many of which are sensitizers [11][12][13][14]. It seems to be rather difficult to produce scented personal care products with fragrances that are not labelled.…”
Section: Sensitizersmentioning
confidence: 99%